Tuntutan Ganti Rugi dalam Perbuatan Melawan Hukum Kepemilikan Hak Atas Tanah : (Studi Di Desa Pilohayanga) - Livya Asifah Magfira Ngabito; Nirwan Junus; Nurul Fazri Elfikri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This research aims to analyze compensation for land rights ownership losses resulting from unlawful acts in view of Article 1541 of the Civil Code in Pilohayanga village. The research method used in this research is empirical legal research using data collection techniques through direct observation and interviews with the litigants. The results of the research show that compensation for ownership of land rights due to unlawful acts in Article 1365 of the Civil Code is mandatory to provide compensation to the person whose fault caused the loss, both in the form of money and compensation in the form of returning it to its original condition. The award of compensation depends on the size of the claim submitted by the injured party. The size of the compensation costs is measured by looking at the object of the dispute, the time limit and the costs incurred in deliberation efforts in the village. However, until now there has been no good intention from the perpetrator to return or compensate for the losses for his actions.